Why Are Arabic Adult Learners in Kuwait Afraid of Making Mistakes in Their English Classroom? - Dashti, Farah; Aysha , Al Mutawa; Adey , Al Bader (European Scientific Journal, ESJ, 2021)
The English language is a second language in Kuwait, and English has been added to the school curriculum with the aim that when students graduate, they will be bilingual in Arabic and English. However, although Arabic adult learners graduate to be fluent in their first language, they struggle in English. This paradox led us to consider specific factors that may inhibit Arabic adult learners from becoming proficient in English when they graduate from high school. One such factor is an unwillingness to speak English in the classroom. The focus of this study, therefore, is to investigate fear of making mistakes as one of factors underlying this unwillingness. Since the study was created during the pandemic, classes in Kuwait, at the time, were taught online only. A questionnaire was given to 210 female Arabic native speakers taking the English foundation course at the College of Basic Education at the Public Authority for Applied Education and Training. The questionnaire focused on factors that might induce a fear of making mistakes when speaking English in the classroom. The results of the study indicated that the most significant factor in this regard was students’ previous experience with English teachers who ridiculed them when they made mistakes in their classes. The findings suggest that when teachers do not take the appropriate approach to motivate students when they make mistakes, this can negatively affect the student’s language learning process.